Crustal deformation and kinematics of the Eastern Part of the North Anatolian Fault Zone (Turkey) from GPS measurements - Tatar, Orhan; Poyraz, Fatih; Gursoy, Halil; Cakir, Ziyadin; Ergintav, Semih; Akpinar, Zafer; Kocbulut, Fikret; Sezen, Fikret; Turk, Tarik; Hastaoglu, Kemal O.; Polat, Ali; Mesci, B. Levent; et al. (Elsevier BV, 2012)
Abstract The North Anatolian Fault Zone (NAFZ) is a 1200 km long dextral strike-slip fault zone forming the boundary between the Eurasian and Anatolian plates. It extends from the Gulf of Saros (North Aegean) in the west to the town of Karliova in eastern Turkey. Although there have been numerous geodetic studies concerning the crustal deformation, velocity field and the slip rate of the NAFZ along its western and central segments, geodetic observations along the eastern section of the NAFZ are sparse. In order to investigate the GPS velocities and the slip rate along the eastern part of the NAFZ, a dense GPS network consisting of 36 benchmarks was installed between Tokat and Erzincan on both sides of the fault zone and measured from 2006 to 2008. Measurement results indicate that the slip rate of the NAFZ increases westwards within about 400 km from 16.3 ± 2.3 mm/year to 24.0 ± 2.9 mm/year, in consistence with the observation that the Anatolian block is being pulled by the Hellenic trench rather than being pushed by the Arabian plate as a result of continental collision between the Arabian and Eurasian plates in eastern Turkey since late Miocene. Modelling the GPS velocities shows that fault locking depth increases also in the same direction from 8.1 ± 3.3 km to 12.8 ± 3.9 km. Slip rate decreases as moving off the Hellenic trench. An average slip rate of 20.1 ± 2.4 mm/year and a locking depth of 12.5 ± 3.5 km are also estimated for the entire study area by using all of the GPS measurements obtained in this study. The GPS velocities are in good agreement with the kinematic models created by paleomagnetic studies in the region and complete the overall picture.
Keywords: Slip rate; Eastern Turkey; GPS velocities; Crustal deformation; North Anatolian Fault Zone